2002
DOI: 10.1177/104973230201200202
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Experiences of Stigma in Relation to Chronic Fatigue Syndrome and Fibromyalgia

Abstract: Chronic fatigue syndrome and fibromyalgia are characterized by being difficult to diagnose and having an elusive etiology and no clear-cut treatment strategy. The question of whether these illnesses are stigmatizing was investigated through interviews with 25 women with these illnesses. The women experienced stigmatization primarily before receiving a diagnosis, and the diffuse symptomatology associated with the illnesses were significant for stigmatization. Stigma consisted of questioning the veracity, morali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
167
0
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(188 citation statements)
references
References 25 publications
11
167
0
10
Order By: Relevance
“…Other research describes delegitimizing as having moral character called into question and being "psychologized" by HPs. 37 In line with the body of research referred to above, participants in the present study described not having their symptoms taken seriously or believed, and having it suggested to them that their symptoms may be the manifestation of an unacknowledged mental health problem. This was particularly problematic especially when the symptoms they were experiencing led to psychological distress.…”
Section: Theme 4: Impact On Mental Health and Role For Psychology-"supporting
confidence: 64%
“…Other research describes delegitimizing as having moral character called into question and being "psychologized" by HPs. 37 In line with the body of research referred to above, participants in the present study described not having their symptoms taken seriously or believed, and having it suggested to them that their symptoms may be the manifestation of an unacknowledged mental health problem. This was particularly problematic especially when the symptoms they were experiencing led to psychological distress.…”
Section: Theme 4: Impact On Mental Health and Role For Psychology-"supporting
confidence: 64%
“…The pain was described as being constant and without any distinct bodily location. Research (Åsbring & Närvänen, 2002; Söderberg et al, 1999) has shown that living with an undiagnosed condition, such as FM, means living in uncertainty and not being seen as a credible person. Being met with disbelief and not being seen as credible harms a person's dignity and causes additional pain (Söderberg et al, 1999).…”
mentioning
confidence: 99%
“…Ware (1992) and Åsbring and Närvänen's (2002) research with people with chronic fatigue syndrome and fibromyalgia, uncovered remarkably similar themes to ours including delegitimization, stigmatization, suffering and contested definitions of illness. Children with chronic pain and their parents told Carter (2002) stories like those of our participants about feeling judged, misbelieved and labeled as difficult or dysfunctional (although among our participants "depressed" or "crazy" were the terms used).…”
Section: The Intersections Of Life Events Emotional Well-being and Tmentioning
confidence: 95%